Aligning Spiritual Values for Meaningful Work: An Empirical Study of Person-Organization Fit in Vietnam - Cao, Thanh Phong (Journal of management, spirituality & religion, 2025)
This study investigates how individual and workplace spirituality contribute to meaningful work through Person- Organization (P-O) spirituality. Drawing on P-O fit theory and workplace spirituality literature, this study proposes that spiritual value congruence enhances employees' perception of meaningful work. Using survey data from 404 full-time employees across diverse industries in Vietnam, the structural equation modeling (SEM) is applied to test the hypotheses. The findings confirm that both individual spirituality and workplace spirituality significantly predict perceived P-O spirituality fit, which in turn strongly influences meaningful work. The study highlights the mediating role of spiritual alignment and underscores its importance in collectivist cultures. Theoretically, this research extends P-O fit literature by integrating spiritual values within a non-Western framework. Practically, it provides actionable strategies for organizations to enhance employee engagement through inclusive and ethically spiritual practices. Limitations and directions for future research, including cross-cultural comparisons and longitudinal designs, are also discussed.